Aquifer Responses to Rainfall through Spectral and Correlation Analysis. (6th November 2018) - Gómez, Derly; Melo, Davi C.D.; Rodrigues, Dulce B.B.; Xavier, Alexandre C.; Guido, Rodrigo C.; Wendland, Edson
Abstract : Research Impact Statement : A framework to estimate the aquifer time lag between precipitation occurrence and its river contribution; it also supports the present and future water allocation in conjunctive water management. Abstract: The response time of hydrological components is an important feature for establishing the connections within a hydrological system and for characterizing it. This study proposes a quantitative and qualitative assessment on the response times of river discharge components, especially the baseflow, regarding the impulse provided by precipitation, using time series analyses of time and frequency domains. To this end, a set of complementary methods including correlation and spectral approaches was used, which are: autocorrelation, cross correlation, continuous wavelet transform, and cross wavelet transform. Such framework was applied in multiple and nested basin scales (53, 1, 867, and 3, 519 km 2 ), located in the Jacaré‐Guaçu River Basin (Southeastern Brazil). Based on a digital filtering technique, it was found the baseflow contributes more than 80% of the annual streamflow, revealing a major role of the aquifer in regulating the river discharge in all three studied basins. In addition, we found baseflow represents a range of 24%–27% of the annual precipitation. The uniform results are mainly due to the similar physical characteristics found in those areas. Overall, our framework indicates a baseflow response time for a precipitation of approximately two years for the smaller basins and three years for the biggest one. Such results can support the water allocation in conjunctive water management, by providing estimates of future surface water availability.